Mechanism of Action and Clinical Application of Tafamidis in Hereditary Transthyretin Amyloidosis. Issue 1 (June 2016) - Coelho, Teresa; Merlini, Giampaolo; Bulawa, Christine; Fleming, James; Judge, Daniel; Kelly, Jeffery; Maurer, Mathew; Planté-Bordeneuve, Violaine; Labaudinière, Richard; Mundayat, Rajiv; Riley, Steve; Lombardo, Ilise; et al.
Abstract Transthyretin (TTR) transports the retinol-binding protein–vitamin A complex and is a minor transporter of thyroxine in blood. Its tetrameric structure undergoes rate-limiting dissociation and monomer misfolding, enabling TTR to aggregate or to become amyloidogenic. Mutations in the TTR gene generally destabilize the tetramer and/or accelerate tetramer dissociation, promoting amyloidogenesis. TTR-related amyloidoses are rare, fatal, protein-misfolding disorders, characterized by formation of soluble aggregates of variable structure and tissue deposition of amyloid. The TTR amyloidoses present with a spectrum of manifestations, encompassing progressive neuropathy and/or cardiomyopathy. Until recently, the only accepted treatment to halt progression of hereditary TTR amyloidosis was liver transplantation, which replaces the hepatic source of mutant TTR with the less amyloidogenic wild-type TTR. Tafamidis meglumine is a rationally designed, non-NSAID benzoxazole derivative that binds with high affinity and selectivity to TTR and kinetically stabilizes the tetramer, slowing monomer formation, misfolding, and amyloidogenesis. Tafamidis is the first pharmacotherapy approved to slow the progression of peripheral neurologic impairment in TTR familial amyloid polyneuropathy. Here we describe the mechanism of action of tafamidis and review the clinical data, demonstrating that tafamidis treatment slows neurologic deterioration and preserves nutritional status, as well as quality of life in patients with early-stage Val30Met amyloidosis.